Surgical management of meningoencephalocele in temporal bone associated with pharmacoresistant epilepsy: report of two cases. (4th March 2019) - Pejović, Aleksa T.; Ristić, Aleksandar J.; Baščarević, Vladimir; Brajković, Leposava; Berisavac, Ivana; Vojvodić, Nikola; Parojčić, Aleksandra; Sokić, Dragoslav
Abstract: We report good outcome after surgical treatment of two patients with meningoencephalocele associated with pharmacoresistant temporal lobe epilepsy. Surgical management of meningoencephaloceles may result in seizure freedom, although optimal surgical strategy is still controversial.